Pengaruh Pengetahuan Ketamansiswaan, Religiusitas, Dan Lingkungan Belajar Terhadap Motivasi Untuk Menjadi Staf Akuntansi Yang Beretika - Aji, Andri Waskita; Prabowo, Adia Adi; Putri, Mey Silvia (Universitas Bandar Lampung (UBL), 2020)
This study discusses the effect of knowledge about ketamansiswaan, religiosity and learning environment on motivation to become ethical accounting staff. The population in this study were accounting students at Sarjanawiyata Tamansiswa University class 2017 and class 2018. The number of samples in this study was taken using purposive sampling method with the criteria of students who have taken the Ketamansiswaan 1 or Ketamansiswaan 2 course and students class 2017 and class 2018. Data sources in this study is primary data. The test method in this study uses the classic assumption test, namely normality test, multicollinearity test, heteroscedasticity test. The results of this study explain this knowledge about ketamansiswaan has a positive effect on motivation to become ethical accounting staff, religiosity has a negative effect on motivation to become ethical accounting staff, while the learning environment also has negative effect on motivation to become ethical accounting staff.